Women for science and science for women: Gaps, challenges and opportunities towards optimizing pre-exposure prophylaxis for HIV-1 prevention - Karim, Quarraisha Abdool; Archary, Derseree; Barré-Sinoussi, Françoise; Broliden, Kristina; Cabrera, Cecilia; Chiodi, Francesca; Fidler, Sarah J.; Gengiah, Tanuja N.; Herrera, Carolina; Kharsany, Ayesha B. M.; Liebenberg, Lenine J. P.; Mahomed, Sharana; et al. (Frontiers in Immunology, 2022)
Preventing new HIV infections remains a global challenge. Young women continue to bear a disproportionate burden of infection. Oral pre-exposure prophylaxis (PrEP), offers a novel women-initiated prevention technology and PrEP trials completed to date underscore the importance of their inclusion early in trials evaluating new HIV PrEP technologies. Data from completed topical and systemic PrEP trials highlight the role of gender specific physiological and social factors that impact PrEP uptake, adherence and efficacy. Here we review the past and current developments of HIV-1 prevention options for women with special focus on PrEP considering the diverse factors that can impact PrEP efficacy. Furthermore, we highlight the importance of inclusion of female scientists, clinicians, and community advocates in scientific efforts to further improve HIV prevention strategies.